Pengaruh Kualitas Layanan, Harga Terhadap Keputusan Pembelian Paket Tour Di PT Dior Travel Lubuk Pakam - Lubis, Risa Kartika (Jurnal Mantik Penusa, 2017)
The purpose of this research is to find the factors that cause tourist interest to use the services of travel agency Dior Tour is very low and arrange alternative strategies and policies that can be implemented by travel agency Dior Travel to increase the number of service users. This type of research is correlational research. Questionnaires were distributed randomly to 100 people who knew and had used the services of the Travel Dior Travel Agency. From result of analysis, it is found that 62,5% decision of purchasing tour package influenced by service quality and price. Variable quality of service, price and word of mouth together have a significant influence to decision of purchasing tour package at Dior Travel But based on partial test, word of mouth variable has no real partial effect to purchase decision. In contrast, service quality variables and price variables significantly influence partial purchasing decisions, and price variables have the most dominant influence on purchasing decisions.